The small business perseverance guide : how to make money and prosper during challenging times - Skevofilax, Manny (Routledge/Productivity Press, 2026)
This book is the result of the author's experiences with the challenges faced by small businesses, including shifting market trends, unstable financial conditions, and the emergence of international catastrophes like pandemics and economic downturns.